Unproductive cetoniinae in Ukrainian language (XI–XIII) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The study of the history of the vocabulary of the Ukrainian language is impossible without studying Stanovlenie separate semantic groups of vocabulary, in particular coloration. The article discusses the functioning of coloration and their derivatives in Ukrainian language (XI – XIII). Fixed allocation of nomina, considered the use of tokens, gray, brown, green in the literal and figurative meanings.
Keywords: cetoniinae; tokens gray; brown; green; colorative; derived words